Oily sludge biodegradation using a new two-phase composting method: Kinetics studies and effect of aeration rate and mode. (April 2019) - Koolivand, Ali; Godini, Kazem; Saeedi, Reza; Abtahi, Hamid; Ghamari, Farhad
Graphical abstract: Highlights: Alternate passive and active aeration presented the highest removal rate of TPH. An overall TPH removal of 90.07–94.23% reached through the two-stage method. The two-phase composting method is efficient in remediation of STOS. Abstract: In this research, the impact of active and passive aeration on the performance of a new two-phase composting process for biodegradation of storage tank oily sludge (STOS) was evaluated. The hyphenated method consisted of primary-stage composting (PSC) including three windrow piles and secondary-stage composting (SSC) including four in-vessel bioreactors. Various turning and aeration rates were tested in the PSC and SSC for 12 and 6 weeks, respectively. Results showed that the removal percentages of total petroleum hydrocarbons (TPH) in the PSC and SSC were in the range of 72.13–89.42 and 68.36–81.63%, respectively. An overall TPH removal of 90.07–94.23% reached through the two-stage system was higher than those of both the PSC and SSC alone. The turning and aeration rate of every 5 days and 1 l min −1  kg −1 were, respectively, determined as optimal values. TPH was degradation fitted to the first-order kinetics based on the rate constants and half-lives of 0.114–0.183 d −1 and 3.79–6.08 days for the PSC, and 0.191-0.296 d −1 and 2.34–3.63 days for the SSC, respectively. The bacteria of Staphylococcus sp., Pseudomonas sp., Proteus sp., and Bacillus sp. were isolated from the process. This study verified the effectiveness of the two-phase composting system in STOS bioremediation.